Análisis de la crisis carcelaria del centro de rehabilitación social varones No.1 de Guayaquil, en el año 2020 - Torres García, Birdman Fernando (2022)
The present research work entitled, analysis of the prison crisis of the male social rehabilitation center No. 1 of Guayaquil, in the year 2020, addresses a problem that has generated a national alarm where the Ecuadorian State has taken temporary corrective measures that have not managed to mitigate the current situation, in this sense we will analyze what have been the factors that have caused instability within the male social rehabilitation center No. 1, which has been subject to changes of administration by each government in power in recent decades, the itself does not prioritize the need to recover the principle of authority in the prison system, the infrastructure of the rehabilitation center is vulnerable, prison officers do not have adequate training to avoid corruption within the center, allowing ppl to have the facility to offending within the rehabilitation center, has caused a crisis that generates inse security and lack of constitutional guarantees for those deprived of their liberty, which is in opposition to what the Comprehensive Organic Criminal Code indicates, referring to the so-called "treatment axes" that have the purpose of giving the tools to rehabilitate those ppl and they can have a comprehensive change to develop and integrate into society.